Moderate Islamic Education as a Space For Negotiating the Religious Identity of Adolescents - Rahman, Mhd. Habibu; Lubis, Sofni Indah Arifa (STAI Serdang Lubuk Pakam, 2025)
Social and religious diversity in Indonesia, especially in rural areas, challenges adolescents' religious identity formation. Teenagers in Tanjung Alam Village, Asahan Regency, live between local religious traditions and the influence of social media and global religious information. This study aims to understand the role of moderate Islamic education as a space for negotiating adolescents' religious identity in Tanjung Alam Village, Asahan Regency. Using a qualitative approach with a case study method, this research explores the experiences of adolescents who live in the midst of local religious traditions and the influence of social media. The results show that moderate Islamic education functions as a dialogical space that allows adolescents to interpret religious values reflectively and contextually. Teenagers learn to balance religious teachings with their social lives, and understand local traditions as part of spirituality that is in line with Islamic teachings. The implication of this research is the need to develop moderate Islamic education as a model of youth character development in Islamic educational institutions. Empathetic, open and critical education needs to be integrated in the curriculum to form a young generation that is religious, tolerant and adaptive to social change without losing their Islamic roots.